Numerical simulation of thermoelectronic thermal protection in the case of high enthalpy flow past a multilayer shell - Efimov, Konstantin N. (Journal of engineering physics and thermophysics)
A mathematical model of the process of unsteady conjugate heat transfer of a thermionic thermal protection system during supersonic air flow around a spherically-blunted cone is investigated Estimates of the effect of evaporation (emission) of electrons from the emitter surface on lowering the temperature of the composite shell of the thermoelectronic thermal protection are made. The influence of different angles of attack on heat transfer modes in the system of multielement thermionic thermal protection has been studied Qualitative agreement of calculated results with the known data has been found.